THE RELATIONSHIP BETWEEN LEADERSHIP CHARACTERISTICS OF SCHOOL ADMINISTRATORS AND ORGANIZATIONAL ENGAGEMENT OF TEACHERS IN CHARITABLE PRIVATE SCHOOLS CHIANG RAI - Songsanti, Pronwijit; Jamjanwong, Jumnong; Ngoenthong, Patcharin (Journal of MCU Nakhondhat, 2023)
The objectives of this research were 1) to study the leadership characteristics of administrators, 2) to study the organizational commitment of teachers, 3) to study the relationship of school administrators’ leadership characteristics and teacher’s organizational commitment. Charity private school Chiang Rai. There were 144 people using the hierarchical random sampling method. The research tools were a questionnaire to study of the relationship between leadership characteristics of school administrators, and a questionnaire. According to Yulk’s concept and Teacher’s organizational commitment According to Allen and Meyer’s concept. The statistics used for research were percentage, mean, standard deviation. and the correlation was determined by Pearson,s correlation coefficient. The results of the study revealed that 1) leadership characteristics of executives. Chiang Rai Charity Private School Overall, The average was at a high level, with an understanding of the situation Followed by the assingnment of roles and responsibilities according to aptitude Giving advice when problems arise Interaction Personnel promotion and support setting rules and regulations for implementation and planning in descending order 2) Teacher’s organizational commitment Chiang Rai Charity Private School overall, it was at a high level. With ties to social norms at the high level followed by mental engagement and persistence commitment with the organization were in the lowest order. 3) The relationship between leadership characteristics of school administrators with teacher organizational engagement charity private school Chiang Rai have a relationship and go in the same direction. When the quality of management is high will result in high relationship with teachers. Statistically significant at the 0.01 level.